البعد المقاصدي وأثره في الفتاو ى المعاصرة فتاو ى الم أ رة عند القرضاوي أنموذجاً - دبار, زينب; تيوه, مسعودة; نسيب, هادية (University of Eloued-جامعة الوادي, 2015)
تناول ه ذ ا البحث أ ث ر المقاصد في الفتوىٰ المعاصرة اوقتصر فيِ د ا رسته ع ل ى ف ت ا وىٰ الم أ رة عند القرضاوي كأنموذجٍ وقد جاء فِي ثلاثة مباحث كان أ وله ا لحقيقة الفتوىٰ تعرِيف ا وأهم ية وضوابِطا بيْ ن م ا عنيّ المبحث الثاني بِال م ق اصِدِ تعريف ا وتقسيما وضوابطا ليخصِّص المبحث الأ خير إلى معالجة قضية من القضايا المهمة التي تخص الم أ رة المسلمة واقتصرنا على مسألتين فقط )ال نق ا ب و خ روجِ ال م أ رة إِلىٰ المسجد(،التي تصدى لها الشيخ يوسف الق رضاوي بإبداء أ ريه وموقفه وفتواه فيها، حيث كانت المقاصد الشرعية،الإطار العام والمسلك الشمولي لبيان أحكامها، وما تضمنه هذا الحكم من مصالح ومنافع جلبا وتحصيلا ، ومفاسد وأض ا رر درءا وابعاداThis research deal , with the impact of perspectives in contemporary fiqh our study refers to fatwa of woman with D.r EL Karadhawi as a model , the research divided into three sections: the first one deal talks about reality , definition , importance and standard of fatwa , in the second section , we explained the reality of Islamic perspective , in sense of definition , division and standard , At the third section we mentioned obstacles that is facing Muslim woman ( the veil , joining to the masjid ) that D.r EL Karadhawi referred to and Dr EL Karadhawi faced these challenges through his opinion , attitudes and fatwa , which means that Islamic perspectives is the general limit and a comprehensive way to explain the rules of Shariah , this is included in that judgment from benefits that is looking for and the harms that is abstaining fro
مذكرة ليسانس
Keywords: البعد المقاصدي / المراة /فتاوى /القرضاوي; La dimension objective / femmes / fatwas / Al-Qaradawi